2006
DOI: 10.1007/s10766-005-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Verification Approach of Metropolis Design Framework for Embedded Systems

Abstract: In this paper, we focus on the verification approach of Metropolis, an integrated design framework for heterogeneous embedded systems. The verification approach is based on the formal properties specified in Linear Temporal Logic (LTL) or Logic of Constraints (LOC). Designs may be refined due to synthesis or be abstracted for verification. An automatic abstraction propagation algorithm is used to simplify the design for specific properties. A user-defined starting point may also be used with automatic propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In most cases, these frameworks are based on the correct-by-construction paradigm and provide a formal support for the whole design process. Metropolis [CHB06] for the Metropolis MetaModel (MMM), SCADE [Ber07], and Ptolemy [EJL + 03] are three examples for these frameworks. All of these approaches focus on system-level design and verification and thus are not applicable for the stepwise refinement process down to register transfer level as used in the HW/SW codesign flow.…”
Section: Verification Frameworkmentioning
confidence: 99%
“…In most cases, these frameworks are based on the correct-by-construction paradigm and provide a formal support for the whole design process. Metropolis [CHB06] for the Metropolis MetaModel (MMM), SCADE [Ber07], and Ptolemy [EJL + 03] are three examples for these frameworks. All of these approaches focus on system-level design and verification and thus are not applicable for the stepwise refinement process down to register transfer level as used in the HW/SW codesign flow.…”
Section: Verification Frameworkmentioning
confidence: 99%
“…The problem of integrating formal verification into the design of DSMLs has been widely addressed by the MDE community. In order to tackle property-based verification problem, authors of [20] present the Metropolis design framework for embedded systems.…”
Section: Related Workmentioning
confidence: 99%
“…Some of them, like the Ptolemy tool [2], don't support a layered abstraction level design approach and use a single specification including both functional behavior and architecture models. Others support the platform-based design approach (like Metropolis [3]) or the top-down design methodology (like SpecC [4]). However, it is demonstrated that the Y-chart layer's based approach, which is followed by several recent works, became nowadays the most popular and used for designing heterogeneous multiprocessors embedded systems.…”
Section: System-level Exploration Tools Comparative Synthesismentioning
confidence: 99%